Comparative Analysis of Small and Medium-Sized Businesses and Its Impact on the Development of Tourism - PARASOTSKAYA, Natalya; BEREZYUK, Valentina; PRASOLOV, Victor; NAZAROVA, Vera; MEZENTSEVA, Tatiana (Journal of Environmental Management and Tourism; Vol 12 No 6 (2021): JEMT Volume XII Issue 6(54) Fall 2021DO - 10.14505//jemt.12.6(54).15, 2021)
In the modern world, the importance of small and medium-sized businesses (hereinafter referred to as SMEs) is increasing in the structure of the national economies of most states, including in the field of tourism, which is one of the main exporters of the economy, contributing to the strengthening of various economic, political, cultural and other relations between countries and regions, and also has the character of a social and economic orientation of the development goals of modern society. SMEs, with the flexibility and ability to adapt, as well as to quickly reorganize them in the face of rapidly changing trends, are the foundation and guarantee of accelerated socio-economic growth.